2009
DOI: 10.3807/josk.2009.13.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Information and Refractive Index Measurement Using a Dual-wavelength Digital Holographic

Abstract: Digital holographic microscopy allows optical path difference measurement. Optical path difference depends on the both refractive index and morphology of sample. We developed a dual-wavelength in-line digital holographic microscope that can measure simultaneously the refractive index and morphology of a sample, providing highly precise three-dimensional information. Here we propose theoretical and experimental methods for dual-wavelength in-line digital holographic microscopy. The measured data were reasonable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A similar complexity would be found if we worked using live cell microscopy. In these cases, where mismatch is significant, it may result in the PSF becoming non stationary, especially along the axial direction [24][25]. Effectively, we have found that embryo raw images present spherical aberrations ( Figure 5 set C, x-z plane).…”
Section: Discussionmentioning
confidence: 88%
“…A similar complexity would be found if we worked using live cell microscopy. In these cases, where mismatch is significant, it may result in the PSF becoming non stationary, especially along the axial direction [24][25]. Effectively, we have found that embryo raw images present spherical aberrations ( Figure 5 set C, x-z plane).…”
Section: Discussionmentioning
confidence: 88%
“…Digital holographic microscopy, because of the direct access to the phase profile, provides highly efficient and versatile phase imaging modality and it is undergoing rapid development. Subnanometer resolution of optical thickness has been demonstrated [13], the refractive index and physical thickness can be separated from the optical thickness [66], and optical phase unwrapping using three LEDs of different wavelengths has been demonstrated [67,68]. The ability to emulate various microscopy methodsincluding bright field, dark field, phase contrast, and DIC, from DHM has also been demonstrated [69].…”
Section: Quantitative Phase Microscopy By Digital Holography (Dhmentioning
confidence: 98%
“…This method of digital recording and reconstruction of a numerical hologram is known as digital holography [7][8][9][10]. Digital holography has many advantages; for example, it does not require any chemical processing because the reconstructed image can be observed easily on a computer monitor, and numerical data can be obtained for three-dimensional (3D) objects [11,12].…”
Section: Introductionmentioning
confidence: 99%